Determinants of Work Motivation in Generation Z: Leadership and Compensation - Putri, Elly; Soejono, Fransiska (Universitas Linggabuana PGRI Sukabumi, 2024)
The purpose of this research is to examine and analyze the influence of leadership style and compensation on the work motivation of Generation Z. This study is an empirical research and based on its explanatory level, it falls into the category of cause-effect research. The research instrument was measured using a Likert scale with five alternative answers. Data collection was conducted using a questionnaire through Google Forms. The total number of respondents was 104 people, but there were 18 individuals who did not meet the criteria (not including Generation Z and not yet employed). Data analysis was performed using the Statistical Package for Research and Teaching (PSPP). The results of this study indicate that leadership does not significantly influence work motivation, while the compensation variable has a positive and significant effect on the work motivation of Generation Z. The implication of this research is the importance of companies providing competitive compensation for Generation Z to motivate them in the workplace. Companies can review their compensation policies and improve recruitment and retention strategies that consider the preferences and values of Generation Z.